Enhancing Online Business Marketing to Expand Market Shares through IT Governance - Sandy Kosasi; Vedyanto Vedyanto; I Dewa Ayu Eka Yuliani (IAES Indonesia Section, 2017)
Online business marketing applied to expand market shares is inextricably connected with availability and reliability of IT governance. This model of marketing covers activities and transactions with a digital mechanism. This research included the sample of 30 MSME (Micro, Small, and Medium Enterprises) businesses of traditional and finished clothes originated in Pontianak City. Stratified sampling technique was applied. In addition, questionnaires with each process divided based upon the levels were in use. These levels were served by using Guttman Scales. The aims of this research were to cognize gap values of maturity levels and propose a recent model of IT governance to reach expected maturity levels. Results show that the lowest values of maturity levels are at PO8 (2.336) and DS5 (2.560). Therefore, redefinition of information architectures, IT resources, quality management, estimation and management of IT risks, system improvement of IT infrastructure management, IT investment strategies, and communication are of great importance. A recommended model shows that PO8 is related to input control objectives PO1, PO10 and ME1 as well as output control objectives AI1, AI2, AI3, AI5, DS2, PO10, AI1, AI2, AI3, AI7, ALL, PO4, and AI6. Meanwhile, DS5 is associated with input control objectives PO2, PO3, PO9, AI2, and DS1 as well as output control objectives DS8, DS7, ME1, AI6, PO9, and DS11.